2012
DOI: 10.1080/13575279.2012.657609
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Work Environment Factors Relating to Burnout Syndrome of Early Childhood Educators in Greece

Abstract: Early childhood education is a profession which requires the professional staff to spend considerable time in intense involvement with other people. The pressure from the demands this profession has can create a sense of physical and emotional exhaustion that often leads to burnout. Thus, previous research has linked perceptions of the work environment to burnout. Despite the fact that burnout was identified as a serious concern in the childcare profession over 20 years ago, limited research has been undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 41 publications
2
21
0
2
Order By: Relevance
“…Those findings are in accordance with a previous research conducted in Greece (Tsigilis, Zachopoulou, and Grammatikopoulos 2006;Rentzou 2012), concerning early childhood educators, and with other studies conducted in other countries (Manlove 1993;Stremmel, Benson, and Powell 1993;Boyd and Schneider 1997). Yet, in Stremmel, Benson, and Powell (1993) and in Tsigilis, Zachopoulou, and Grammatikopoulos (2006) studies only the emotional exhaustion subscale was used and compared to the other studies, the educators of the present study reported that they maintain lower levels of personal accomplishment.…”
Section: Discussion and Recommendationssupporting
confidence: 95%
See 4 more Smart Citations
“…Those findings are in accordance with a previous research conducted in Greece (Tsigilis, Zachopoulou, and Grammatikopoulos 2006;Rentzou 2012), concerning early childhood educators, and with other studies conducted in other countries (Manlove 1993;Stremmel, Benson, and Powell 1993;Boyd and Schneider 1997). Yet, in Stremmel, Benson, and Powell (1993) and in Tsigilis, Zachopoulou, and Grammatikopoulos (2006) studies only the emotional exhaustion subscale was used and compared to the other studies, the educators of the present study reported that they maintain lower levels of personal accomplishment.…”
Section: Discussion and Recommendationssupporting
confidence: 95%
“…Yet, in Stremmel, Benson, and Powell (1993) and in Tsigilis, Zachopoulou, and Grammatikopoulos (2006) studies only the emotional exhaustion subscale was used and compared to the other studies, the educators of the present study reported that they maintain lower levels of personal accomplishment. The results of the present study confirm, however, previous research results from Greece (Koustelios and Kousteliou 2001;Kokkinos 2006), which were conducted with elementary and secondary school teachers and with the study conducted by Rentzou (2012) with early childhood educators.…”
Section: Discussion and Recommendationssupporting
confidence: 91%
See 3 more Smart Citations